Design and Implementation of Efficient Analysis and Synthesis QMF Bank for Multicarrier Cognitive Radio Communication. - Ankur Singh Kang; Renu Vij (Universitas Ahmad Dahlan, 2017)
The present section deals with a new type of technique for designing an efficient two channel Quadrature Mirror Filter Bank with constant phase in frequency. For achieving the Perfect Reconstruction Condition in Filter bank, an attempt has been made to design the low pass prototype filter with its impulse response and frequency response in three regions namely pass band, stop band and transition band region. With the error in terms of Reconstruction and the attenuation in the stop band as seen in the prototype filter response, one can evaluate the performance of the introduced filter with the help of filter coefficients generated in the design examples that affects the quality of filter bank design under the constraints of Near Perfect Reconstruction Conditions.